Capacity Building on Waste Management and TrashGo Application Utilization for the Community in Joglo, Surakarta - Nani Irma Susanti; Yusuf Sutanto; Adnan Terry Suseno; Heribertus Ary Setyadi (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: The transaction mechanism for scrap items designates collectors as the purchasing party and community members or scavengers as the selling party. In operating their business, they still rely on manual methods, involving circulating door-to-door and relying on phone calls from regular customers. The current situation requires residents to wait for collectors to circulate their area and leaves them uninformed about the unpredictable and unstable pricing of scrap goods.Aims: This study aims to provide education provision regarding waste and scrap, followed by a workshop detailing the operation of the TrashGo application that was developed during prior activities.Methods: Asset-Based Community Development (ABCD) which consists of five stages: discovery, dream, design, define, and destiny.Result: Participants understood the business side of waste and scrap. Both collectors and the community were able to effectively utilize the TrashGo application for conducting scrap material transactions. A 95% level of understanding regarding the scrap business and application usage was achieved, signifying the training's success and utility.Conclusion: Data from questionnaires filled out by all participants show that this activity's targets were met. Based on the satisfaction survey, it can be concluded that participants were pleased and felt supported by the program.